Herpes zoster following COVID-19 asymptomatic infection in children. - Reza, N.R.; Prakoeswa, C.R.S.; Alkaff, F.F. (European Journal of Pediatric Dermatology, 2022)
There is a growing literature on the possible association between SARS-CoV-2 coronavirus 2019 (COVID-19) infection and herpes zoster (HZ). However, reports of HZ in pediatric patients following COVID-19 infection are still scarce. We present the case of a four-year-old patient with vesicular eruption of the right hemithorax. The patient had a history of primary varicella zoster virus (VZV) infection at the age of one year. No prodromal symptoms were reported prior to the onset of the vesicular rash. Three weeks earlier, some family members had been diagnosed with COVID-19, while the patient had tested negative on the molecular test and exhibited no symptoms of COVID-19. However, the quantitative titer of IgG antibodies was high. The patient received a diagnosis of HZ and was treated with acyclovir. Current report shows that HZ could occur in immunocompetent children following asymptomatic COVID-19 infection. Physicians should therefore be aware of the possible relationship between HZ and COVID-19, even when the molecular test is negative.